Persepsi Siswa Terhadap Perilaku Seksual Remaja di Kota Palembang - S Supriyanto; Gita Isyanawulan; Syafruddin Yusuf (Master Program in Sociology, Faculty of Social and Political Science, Universitas Sriwijay, 2018)
Teenagers have a high curiosity, among them is a matter of sexuality. Teen curiosity about sexuality is due to the development of adolescents entering puberty which is characterized by the maturation of the reproductive system and the production of sex hormones. This study aims to determine students' perceptions of adolescent sexual behavior in the city of Palembang. The research used a descriptive quantitative research design with cross sectional approach. The sample in this research are some students of SMA Srijaya Negara and SMA Negeri 1 Palembang as many as 214 people by using simple random sampling. The data were collected by using questionnaires. Statistical test used is product moment correlation to test the influence between variables. The results obtained that there is influence of students' perceptions on adolescent sexual behavior. If the attitude of adolescents have a positive perception of adolescents do not intend to engage in sexual behavior before marriage. Teenagers can maintain and improve knowledge by being able to sort and filter information obtained from the mass media about sexual behavior.